(untitled) (Ágora Journal, 2025)
This paper, through a series of works of art from the Netherlands, explores the construction of the concept of “jurist” in the context of the Ancien Regime, which came to reflect the structure of the Western juridic culture. From the professionalization of law and the rediscovery of Corpus Iuris Civilis and Corpus Iuris Canonici, it is observed the substitution of customary law by a codified normative system and academic character. In this light, the essay highlights the strategic use of art not only as an instrument for self-legitimizing jurists, but also as a vehicle for forceful criticism of this class through an iconographic analysis. Thus, the author shows that even after almost a millennium of the introduction of the Roman-canonical procedure, and almost five hundred years after the artistic representations criticizing the system, many of the structural problems of the legal field remain the same in contemporaneity.